Preventing single-use plastic waste Implications of different policy approaches - Cornago, Elisabetta (OECD Environment Working Papers, 2021)
Single-use plastics constitute approximately half of global plastic waste generation. Their use in consumer goods and packaging has been the focus of recent waste prevention policy due to the importance of the volumes of waste generated and the frequency with which these materials are littered. To address several externalities that emerge across the life-cycle of single-use plastics, multiple policies can be combined to constitute an effective policy mix. In several markets, market-based policy instruments and policy bans have helped to curb waste generation and littering of single-use plastics. However, the effectiveness of these interventions depends to an important extent on whether environmentally preferable substitute materials or products are available, and on whether the measures are effectively enforced. Effective policy intervention requires a policy mix that covers single-use plastics, as well as their substitutes, and that includes an emphasis on monitoring and enforcement, in order to help minimise burden-shifting of environmental impacts